Prevalence and factors associated with childhood malaria and anaemia in Osun state, Nigeria: a baseline household malariometric study - Olusola Ajibaye; Semiu Adebayo Rahman; Oluwagbemiga Olanrewaju Aina; Chinazo Ujuju; Chimere Obiora Agomo; Samuel Akindele; Olakiigbe Abiodun; Tolulope Victoria Uzoka; Nnenna Ogbulafor; Olufemi Oroge; Rufai-Ahmed Garba; Michael Ekholuenetale; et al. (Malaria Journal)
Abstract Background Under-5 children have been known to bear a significant burden of malaria in endemic countries. Though significant progress has been made towards malaria prevention and control in Nigeria, it is expected that the addition of new malaria prevention strategy, such as perennial malaria chemoprevention (PMC) can contribute to a more rapid decline in malaria cases. This study aimed to determine the prevalence and factors associated with malaria and anaemia among children aged 2–18 months in Osun State. Methods A cross-sectional household malariometric study was conducted in 80 communities across eight Local Government areas (LGAs) in Osun State. Ethical approval was obtained from Osun State Health Research Ethical Committee (OSHREC/PRS/569T312/ on the 22nd of May 2023. Malaria test positivity was determined by rapid diagnostic test (RDT) and microscopy. In addition, haemoglobin levels were measured using Haemocue® Hb 201. Caregivers were interviewed on malaria management practices using tools adapted from Nigeria Malaria Indicator Survey. Results A total of four hundred children aged 2–18 months were assessed in this study, which was conducted in July 2023. The caregivers were mostly the biological mothers of the children (n = 387, 96.8%). Female children were 51.8% and their male counterparts 48.2% respectively. Malaria positivity rate by RDT was 36.8% and this was higher in children aged 13–18 months (48.0%) and followed by those aged 7–12 months (44.0%). By microscopy, the positivity rate was 12.5% overall, with 15.0% positivity rate among children aged 7–12 months, about 13.5% among those 13–18 months and those aged 2–6 months had the least positivity rate whether by microscopy (8.5%) or RDT (18.5%). Overall, the prevalence of severe anaemia was 4.0%, moderate was 37.3%, mild was 18.3% and the normal was 40.4% respectively. However, higher proportion of moderate anaemia (7.0–9.9 haemoglobin (g/dL)) was reported in older children. Children from medium wealth households (aOR = 0.549; 95% CI 0.306–0.986) and those from rich households (aOR = 0.543; 95% CI 0.283–1.042) had 45.0% reduction in the odds of having malaria, when compared with their counterparts from poor households. In addition, children aged 7–12 months (aOR = 2.856; 95% CI 1.524–5.354) and those aged 13–18 months (aOR = 4.269; 95% CI 2.422–7.526) had higher odds of malaria infection, respectively, when compared with children aged 2–6 months. Conclusion Malaria infection and anaemia were found to be higher in older children. Household wealth and child’s age were significantly associated with malaria infection. These findings would inform the positioning of PMC intervention touch-points to reduce malaria burden in young children.